Association Between Carotid Artery Function and Structure in the Northern Manhattan Study - Della-Morte, David; Gardener, Hannah; Dong, Chuanhui; Markert, Matthew; Cabral, Digna; Elkind, Mitchell S. V.; Sacco, Ralph L.; Rundek, Tatjana (Frontiers in Neurology, 2018)
Background and Purpose – Carotid plaque (CP), carotid intima media thickness (cIMT) and stiffness (STIFF) are pre-clinical markers of atherosclerosis and predictors of cerebrovascular disease (CVD). We sought to investigate weather STIFF is a significant determinant of cIMT and CP, which may provide an insight into the mechanism by which STIFF adds to the risk of CVD. Methods – We analysed 876 stroke-free subjects from the Northern Manhattan Study with available ultrasound measures. To obtain the associations with STIFF, we performed multivariable-adjusted regression, negative binomial regression (for CP number) and multinomial logistic regression (for plaque area). Results – The mean age was 64±9 years; 63% women, and 65% Caribbean Hispanics. The mean cIMT was 0.93±0.9mm, the mean diastolic diameter 6.24±0.94mm, and STIFF 8.6±6.2lnmmHg. Prevalence of CP was 57%, and the mean total plaque area was 22.6±23.0mm2. STIFF was positively associated with cIMT, but not with CP. There was an association between diastolic diameter and thick plaque. For each mm increase in diastolic diameter, there was about a 20% increased risk of having thick plaque (vs. no plaque). In longitudinal analyses, each mm increase in diastolic diameter was associated with a 37% increased risk of incident plaque. Conclusion – Increased STIFF was associated with increased cIMT, and carotid artery dilatation with greater plaque burden. Increased cIMT and plaque burden represent vascular remodelling likely resulting from the two different age-related mechanisms, one that includes diffuse wall thickening (cIMT) with stiffness, and another that incorporates focal atherosclerosis (plaque) with luminal dilatation.